(untitled) (Baltic Journal of Sport and Health Sciences, 2022)
Background: This article discusses the current knowledge on the effects of heat stress on cognitive abilities. Whole-body hyperthermia (WBH) has a negative effect on mental performance. In this study, we investigated whether short-term whole-body immersion in water at 45°C (HWI-45°C), which induces a strong neurotransmitter and temperature flux without inducing whole-body hyperthermia, would impair mental performance in humans. Methods: Fourteen men (aged 25±6 years) were enrolled in this study and participated in three experiments: (i) a brief (5-min) immersion of the whole body in 37°C water (WI-37°C); (ii) a brief (5-min) immersion of the whole body in 45°C water (HWI-45°C); and (iii) a control trial in a thermoneutral condition at an ambient temperature of 24°C and 60% relative humidity. Before and after immersion, cognitive performance was tested. All tests were performed in a quiet and semi-darkened laboratory. Results: Baseline simple, 2-choice and procedural reaction time and percentage of correct answers did not differ significantly across all trials. 2-choice reaction time was reduced (i.e. faster reaction) only after immersion to 37°C water. Interestingly, only whole-body immersion to 45°C was a sufficient trigger to reduce procedural reaction time. Conclusion: young healthy men do not deteriorate in response to whole-body hot water immersion for a short duration. By contrast, we here show faster reaction time in procedural reaction task, which was the most difficult of the three to perform. Keywords: Heat stress, hot water immersion, cognitive performance.